SOCIAL VALUES IN THE NOVEL SUNSET WITH ROSIE BY TERE LIYE - Harahap, Andi Syahputra; Muliatik, Sri (LUMBUNG AKSARA, 2024)
The novel Sunset with Rosie by Tere Liye captures the setting of the impact of the bomb that occurred in Bali regarding the lives of Tegar and Rosie's family. There are many social values ​​that can be found in the novel. Tegar's sincerity in leaving his new life in Jakarta to look after Rosie and her children, the relationship between Tegar and Rosie's children, the willingness of Rosie's children not to hate the Bali Bombing perpetrators, and so on. Based on the quote above, researchers are interested in researching the social values ​​contained in the novel Sunset Bersama Rosie by Tere Liye, because nowadays social criticism has become a problem that requires a lot of action. Especially in the world of learning. The title of the scientific work is "Analysis of Social Values ​​in the Novel Sunset Bersama Rosie by Tere Liye" The aim of this research is to describe the Social Values ​​contained in the novel Sunset Bersama Rosie by Tere Liye. The research method used in this research is descriptive qualitative research by analyzing the analysis of social values ​​in the novel Sunset with Rosie by Tere Liye. The object of research is the novel Sunset with Rosie by Tere Liye. The value contained in the novel Sunset with Rosie by Tere Liye is something that encourages a person to be better. The types of social values ​​contained in the novel Sunset with Rosie by Tere Liye contain three forms of social values, namely social values ​​towards God, oneself and fellow humans. Social values ​​of human relationships with God such as gratitude, sincerity and accepting fate. Social values ​​of human relationships with oneself such as, Never Giving Up, Responsibility, Humility, Independence and Honesty. The social values ​​of human relationships with fellow human beings include, please help, respect others, care for each other, remind each other, be willing to make sacrifices, and be alert. Of the three social values ​​contained in the novel Sunset Bersama Rosie, the social value is the most dominant in the novel Sunset Bersama Rosie by Tere Liye is the social value of human relations between humans. This is because there is a lot of social interaction carried out in the novel involving the main character and other characters which creates social interaction between humans.